DAMPAK USAHA PERIKANAN BUDIDAYA TERHADAP KONDISI LINGKUNGAN DAN SOSIAL EKONOMI MASYARAKAT PADA LAHAN PASANG SURUT KABUPATEN BANYUASIN PROPINSI SUMATERA SELATAN - Tike Dwi Putri; Dwi Putro Priyadi; Sriati . (Universitas Sriwijaya, 2014)
ABSTRACT The purpose of this study is to analyze the business impact of aquaculture on water quality conditions and socio-economic communities in Cinta Manis Lama Village District of Banyuasin I Banyuasin district. This research was conducted in Cinta Manis Lama Village Subdistrict Banyuasin I Banyuasin district, in March to May 2012.The results show refers to the South Sumatra Governor Regulation 16 of 2005, the results of water quality analysis that is on standard quality parameters including temperature (280C-310C), COD (0.32 mg/l-3.87 mg/l) and ammonia (0.00198 mg/l-0.22280 mg/l). While under the quality standard parameters include pH at Station 4 (5.0 and 5.5), DO at Station 4 (4.88 mg/l and 5.02 mg/l), BOD5 at all observation stations (3.09 mg/l-4.82 mg/l) and total phosphate at all observation stations (0.03546 mg/l-0.19980 mg/l). The results also show that the aquaculture business is conducted in Cinta Manis Lama village can increase the percentage increase in income of at least 22.22% to 250% and also improve relations/social interaction. Â Keywords: aquaculture, water quality, socio-economic